Rethinking environmental leadership: The social construction of leaders and leadership in discourses of ecological crisis, development, and conservation. (November 2015) - Case, Peter; Evans, Louisa S; Fabinyi, Michael; Cohen, Philippa J; Hicks, Christina C; Prideaux, Murray; Mills, David J
Leadership is heralded as being critical to addressing the "crisis of governance" facing the Earth's natural systems. While political, economic, and corporate discourses of leadership have been widely and critically interrogated, narratives of environmental leadership remain relatively neglected in the academic literature. The aims of this paper are twofold. First, to highlight the centrality and importance of environmental science's construction and mobilization of leadership discourse. Second, to offer a critical analysis of environmental sciences' deployment of leadership theory and constructs. The authors build on a review of leadership research in environmental science that reveals how leadership is conceptualized and analyzed in this field of study. It is argued that environmental leadership research reflects rather narrow framings of leadership. An analytical typology proposed by Keith Grint is employed to demonstrate how any singular framing of environmental leadership as person, position, process, result, or purpose is problematic and needs to be supplanted by a pluralistic view. The paper concludes by highlighting key areas for improvement in environmental leadership research, with emphasis on how a political ecology of environmental crisis narratives contributes to a more critical body of research on leadership in environmental science.